P-BN12 Impact of covid-19 on ugi (upper gastrointestinal) tract stenting and dilatation services- prioritise, keep scoping and training. (16th December 2021) - Yau, Chia Chuin; Esmaily, Shiran; Dwarakanath, Deepak; Hancock, John; Mitra, Vikramjit
Abstract: Background: The COVID-19 pandemic profoundly affected endoscopy services including therapeutic gastroscopy across the UK. The BSG (British Society of Gastroenterology) issued guidance for managing endoscopy services safely throughout this period. At the beginning of the pandemic in March 2020, a symptom-based questionnaire was used to screen patients for COVID-19 prior to their endoscopic procedures in our hospital (COVID-19 swabs were only carried out if patients presented with COVID-19 symptoms). From 18 May 2020 onwards, in addition to the above approach, all patients attending endoscopic procedures underwent a SARS-CoV-2 nasopharyngeal swab 1-3 days prior to the procedure. We describe our experience of UGI stenting and dilatation during the initial wave of COVID-19 pandemic in the UK.  Aims: To assess the impact of COVID-19 pandemic on technical and clinical success of luminal dilatation and stenting in the UGI tract and ascertain the risk of procedure related complications. Methods: A retrospective audit of a prospectively maintained endoscopy database was carried out between 18th March and 31st July. All patients were followed for 30 days. Full PPE were used. Results: 42 procedures [31 were oesophageal dilatation (21 peptic stricture, 9 radiotherapy stricture, 1 achalasia), 8 oesophageal stent insertion (6 for primary oesophageal cancer, 1 metastatic cancer and 1 secondary to external compression from lung cancer) and 3 pyloric dilatation all benign] were carried out-mean age 65 years, 64.3% males, 81% of procedures were carried out as outpatients. All procedures were performed under fluoroscopy. 41/42(97.6%) patients had a confirmed histology prior to their procedure – one patient who underwent oesophageal dilatation had a peptic stricture on endoscopy (no biopsy or imaging). 39/42(92.9%) patients had undergone CT scan and/or barium swallow prior to their first procedure. All procedures were technically and clinically successful (100%).There were no procedure related complications or mortality. There were no COVID positive swabs in the 30-day post procedure period during the entire study period. Trainees were present in 21/42 (50%) of the procedures. None of the endoscopists who were involved with these procedures were diagnosed with COVID-19 during this period. One of the nursing staff, who regularly assisted in the fluoroscopy room, was involved in a non-fluoroscopic endoscopic procedure in a COVID-19 patient (not known at the time of the procedure) and subsequently tested positive.  Conclusions: Our study confirms that a high quality stenting and dilatation service of the upper gastrointestinal tract together with specialist registrar training can be delivered safely and effectively during the COVID-19 pandemic in appropriately prioritised symptomatic patients.